Enhanced thermophysical properties of Metal oxide nanoparticles embedded magnesium nitrate hexahydrate based nanocomposite for thermal energy storage applications. (December 2020) - Gupta, Neeraj; Kumar, Amit; Dhasmana, Hrishikesh; Kumar, Vivek; Kumar, Avshish; Shukla, Prashant; Verma, Abhishek; Nutan, Gautam V.; Dhawan, S.K.; Jain, V.K.
Highlights: Inorganic salts hydrate based, PCM-metal oxide nanocomposites were prepared by simple melt mixing techniques. Different metal oxides nanoparticles were used to enhanced the heat transfer rate with in the matrix of the PCM. The addition of TiO2 nanoparticles enhanced the thermal conductivity by 147.5.% PCM-metal oxide nanocomposites show improvement in extent of supercooling and thermal energy storage capacity. The 0.5 wt.% was the optimal concentration of the nanoparticles to improve the thermophysical properties. Results confirms the suitability of prepared nanocomposite in instant solar water heating application. Abstract: This paper investigates the effect of metal oxide (MOx) nanoparticles on thermophysical properties of phase change material (PCM) for thermal energy storage applications. Different types of (MOx) nanoparticles include Titanium di-oxide (TiO2 ), Zinc oxide (ZnO), Ferric oxide (Fe2 O3 ) and Silicon di-oxide (SiO2 ) were added independently in the magnesium nitrate hexahydrate, an inorganic salt hydrate PCM, to form PCM-metal oxide nanocomposite by melt mixing technique. The scanning electron microscopy was done to investigate the shape and morphology of nanoparticles and their uniform distribution in the PCM matrix. Structural and interaction between nanoparticles and PCM were analyzed by X-ray diffraction (XRD) and Fourier transformed infrared (FTIR) spectroscopic techniques, respectively. The cyclic stability of the prepared nanocomposites was confirmed by thermogravimetric analysis. Nanoparticles concentration in the PCM matrix is very crucial and needs to be carefully optimized to maximize the thermal conductivity enhancement and herein we found that 0.5 wt.% of NPs in PCM matrix show promising thermophysical properties. Thermal conductivity of PCM-metal oxide nanocomposites was improved by 147.5%, 62.5%, 55% and 45% by the addition of 0.5 wt.% TiO2, ZnO, Fe2 O3 and SiO2, respectively. The addition of nanoparticles modified the phase change process of PCM nanocomposites and also reduced the phase change temperature range. Besides thermal conductivity enhancement, these also eliminate supercooling while maintain the latent heat capacity. The heat transfer characteristics of PCM-metal oxides nanocomposites were analyzed by conventional heating systems. The PCM-TiO2 nanocomposite demonstrates the best heat transfer characteristics and reduces the phase transition time performances amongst the other metal oxide nanoparticles. It was found that the charging and discharging rate increased by 33% and 77.5% respectively, upon using 0.5 wt.% TiO2 in comparison to pristine PCM and used as a potential material in instant solar water heating system for solar thermal energy storage application. Graphical abstract: Thermal conductivity of PCM nanocomposite depends upon various properties of nanomaterials. Metal oxide nanomaterials dispersed uniformly in the PCM matrix. Highest enhancement in the thermal conductivity is recorded in case of TiO2 bases composite, thereby considerable enhancement in charging rate Image, graphical abstract .